Interrelated Demands for Buffer Stocks and Productive Inputs: Estimates for Two-Digit Manufacturing Industries - Rossana, Robert J. (The Review of Economics and Statistics, 1990)
Robert J. Rossana, Interrelated Demands for Buffer Stocks and Productive Inputs: Estimates for Two-Digit Manufacturing Industries, The Review of Economics and Statistics, Vol. 72, No. 1 (Feb., 1990), pp. 19-29